The Expanded Body and the Fragmented Body: Inside and Beyond Narrative - Pandolfi, Maria (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1992)
A rethinking of anthropology in terms of Gramsci's account of resistance with special focus on the example of witchcraft in Italy.